High performanse relational database design - Kirkwood, John (Ellis Horwood series in computer and their applications, 1992)
This book shows how to create high performances relations databases designs. It concentrates on making database designs work showing how to move away from the relational rules to achieve high performance and outlining practical ways of circumventing difficulties thrown up by the theory.